Educated Persons in India, 1955 May : 1958 Manpower Studies-9 - Planning Commission (Planning Commission, 1968)
The 1955 Manpower Studies on Educated Persons in India provide a detailed examination of educational demographics and employment patterns across urban and rural regions. With approximately 4.7 million educated individuals, the study highlights stark gender and regional disparities, with men dominating both education and labor force participation. Employment was concentrated in the public sector, while graduate unemployment showed a rising trend, particularly among women and younger age groups. Analysis reveals gaps in registration and underutilization of skills, emphasizing the need for targeted policies to enhance educational access, align training with labor market demands, and reduce unemployment. These findings inform strategic planning for workforce development and socio-economic equity in India.
Planning Commission Perspective Planning Division Manpower Studies 9
Planning Commission Perspective Planning Division Manpower Studies 9
Keywords: Educated Persons; India; Manpower Studies; Employment Status; Unemployment; Gender Disparities; Rural-Urban Differences; Labor Force Participation; Graduate Unemployment; Public Sector Employment; Educational Attainment; Policy Implications